Long-run effects of austerity - Guilherme Klein Martins (University of Massachusetts, Department of Economics, 2022)
This paper provides evidence that austerity shocks have long-run negative effects on GDP. Besides addressing the important gap in the growing fiscal research regarding the short time horizon of the estimations, this paper analyzes two other important assumptions made in the literature regarding the (i) symmetry of episodes of fiscal expansion and con- traction and (ii) uniformity of fiscal multipliers for different sizes of shocks. We use narrative fiscal shocks and propensity score reweighting in a local projections setup to account for the potential endogeneity of austerity policies and the non-linearity of its effects over time. The estimation is also adapted to eliminate the bias that emerges when multiple shocks might oc- cur within the time horizon of interest. Our baseline results show that contractionary fiscal shocks larger than 1.5% of GDP generate a negative effect of more than 3% on GDP even after 15 years. The drop in GDP reaches 5.5% for fiscal contractions larger than 3%. Evidence is also found linking austerity with smaller capital stock in the long-run. The results are robust to different fiscal shocks datasets, the exclusion of particular countries and shocks, alternative estimation methods, and the use of cleaner controls. Besides understanding the consequences of this particular policy, the results contribute to the broader discussion on the long-run effects of demand by suggesting that such shocks might permanently affect the economy.
Keywords: C54; E62; H5; H2; 330; austerity; long-run; fiscal policy; multipliers